Physicochemical characterization of inorganic deposits associated with granulomas in cutaneous sarcoidosis. (31st July 2018) - Colboc, H.; Moguelet, P.; Bazin, D.; Bachmeyer, C.; Frochot, V.; Weil, R.; Letavernier, E.; Jouanneau, C.; Daudon, M.; Bernaudin, J.F.
Abstract: Background: Sarcoidosis, characterized by epithelioid granulomas, is considered to be caused by a complex interplay between genetics and environmental agents. It has been hypothesized that exogenous inorganic particles as crystalline silica could be a causal or adjuvant agent in sarcoidosis onset. Objectives: To investigate the location, frequency and physicochemical characteristics of foreign materials and mineral tissue deposits in the granulomatous area of cutaneous sarcoidosis. Methods: Skin biopsies ( n = 14) from patients diagnosed with cutaneous sarcoidosis (mean age 43 years; 11 patients with extracutaneous involvement) were investigated using polarized light examination (PLE), μFourier Transform Infra‐Red (μFT‐IR) spectroscopy and Field Emission Scanning Electron Microscopy coupled with Energy Dispersive X‐ray Spectroscopy (FE‐SEM/EDX). Results: Combined PLE, μFT‐IR, FE‐SEM/EDX analysis allowed to characterize mineral deposits in 7/14 biopsies (50%). It identified crystalline silica (SiO2 ) inside granulomas in three biopsies and calcite (CaCO3 ) at their periphery in 4. Conclusion: This study emphasizes the need of using combined methods for assessment of mineral deposits in granulomatous diseases. According to the location and characteristics of deposits, we can hypothesize that SiO2 particles contribute to the granuloma formation, whereas CaCO3 deposits are related to the granuloma biology. However, the significance of the association between SiO2 deposits and sarcoidosis is still disputed.